Specific Targeting of Notch Ligand-Receptor Interactions to Modulate Immune Responses: A Review of Clinical and Preclinical Findings - Goruganthu, Mounika U. L.; Shanker, Anil; Dikov, Mikhail M.; Carbone, David P. (Frontiers in Immunology, 2020)
Understanding and targeting Notch signaling effectively has long been valued in the field of cancer and other immune disorders. Here, we discuss key discoveries at the intersection of Notch signaling, cancer and immunology. While there is a plethora of Notch targeting agents tested in vitro, in vivo and in clinic, undesirable off-target effects and therapy-related toxicities have been significant obstacles. We make a case for the clinical application of ligand-derived and affinity modifying compounds as novel therapeutic agents and discuss major research findings with an emphasis on Notch ligand-specific modulation of immune responses.